Stability-indicating HPLC and PLS chemometric methods for the determination of acemetacin in presence of its degradation products and impurities - Kessiba, Amira Mohamed; Hegazy, Maha Abdel Monen; Abdelkawy, Mohamed Mohamed; El Gendy, Ahmed Emad (European Journal of Chemistry, 2015)
Two stability-indicating methods were developed and validated for the quantitative determination of acemetacin (ACM) in presence of its degradation products and impurities. The first method was based on separation of ACM from its degradation products and impurities by RP-HPLC on Inertsil C8 column (150 × 4.6 mm i.d) using a mobile phase composed of 0.02 M phosphate buffer: methanol (35:65, v:v, pH = 6.5). The flow rate was adjusted at 1 mL/min and quantification was achieved with UV detection at 245 nm using meloxicam as internal standard. The second method was based on multivariate spectrophotometric analysis using partial least square regression model. The drug was subjected to acid, base, oxidative and thermal stress conditions and the degradation products were identified. The developed methods have the requisite accuracy, selectivity, sensitivity and precision to assay ACM in presence of its degradation products and impurities either in bulk powder or in pharmaceutical dosage form. The results obtained for the analysis of ACM in its pure form by the proposed methods were statistically compared to those obtained by applying a reported HPLC method. The statistical comparison showed that there is no significant difference between the proposed methods and the reported one with respect to accuracy and precision.